Trauma and Emergency Surgery - Sözen, Selim; Hakan Kanat, Burhan (IntechOpen, 2022)
Trauma surgery is a surgical specialty that utilizes both operative and non-operative management to treat traumatic injuries, typically in an acute setting. The trauma surgeon is responsible for initially resuscitating and stabilizing and later evaluating and managing the patient. Emergency surgery is surgery to treat trauma or acute illness after an emergency presentation. This book examines trauma and emergency surgery for abdominal, aortic, chest, brain, and burn injuries.